A new species of Eurytoma (Hymenoptera: Eurytomidae) attacking Quadrastichus spp. (Hymenoptera: Eulophidae) galling Erythrina spp. (Fabaceae), with a summary of African Eurytoma biology and species checklist - Gates, M.; Delvare, G. (Zootaxa, 2008)
Eurytoma erythrinae Gates and Delvare, new species, is described and illustrated. This species was reared from fieldcollected galls on Erythrina spp. (Fabaceae) induced by Quadrastichus spp. (Hymenoptera: Eulophidae), in Tanzania, Ghana, and South Africa. It is compared with very similar African species, Eurytoma radicicola Risbec. Afrotropical species classified in Eurytoma are reviewed and twenty-seven new combinations are proposed: Aximopsis acaciacola (Hedqvist) comb. n., A. caryedocida (Rasplus) comb. n., A. lamtoensis (Rasplus) comb. n., A. mateui (Hedqvist) comb. n., A. mimosarum (Rasplus) comb. n., A. obocki (Risbec) comb. n., A. oryzivora (Delvare) comb. n., A. saharensis (Hedqvist) comb. n., A. senegalensis (Risbec) comb. n., A. tropicana (Risbec) comb. n., Bruchophagus conapionis (Rasplus) comb. n., Fronsoma ellenbergeri (Risbec) comb. n., Gibsonoma amborasahae (Risbec) comb. n., G. aphloiae (Risbec) comb. n., G. bararakae (Risbec) comb. n., G. eugeniae (Risbec) comb. n., G. mandrakae (Risbec) comb. n., G. pauliani (Risbec) comb. n., G. plectroniae (Risbec) comb. n., G. tavolae (Risbec) comb. n., Philolema arachnovora (Hesse) comb. n., P. arnoldi (Waterston) comb. n., P. bambeyi (Risbec) comb. n., P. braconidis (Ferrière) comb. n., and P. syleptae (Ferri_re) comb. n., Phylloxeroxenus cressoni (Howard) comb. n., and Sycophila plectroniae (Risbec) comb. n. Lectotypes are designated for ten species: Eurytoma perineti Risbec, E. radicicola Risbec, E. toddaliae Risbec, Gibsonoma amborasahae (Risbec), G. aphloiae (Risbec), G. eugeniae (Risbec), G. mandrakae (Risbec), G. pauliani (Risbec), G. tavolae (Risbec), and P. bambeyi (Risbec). We also provide a checklist of Afrotropical species that are or were classified in Eurytoma and tabulate the known host/associations of these species with references.